Participation in Agricultural Extension - World Bank (Washington, DC, 2012)
Putting responsibility in the hands of farmers to determine agricultural extension programs can make services more responsive to local conditions, more accountable, more effective, and more sustainable. To realize these benefits, the role of the public sector has to be redefined to permit multiple approaches which account for user diversity, and to develop partnerships with farmer organizations, nongovernmental organizations, and the private sector for service delivery.